Anti-aging function and molecular mechanism of Radix Astragali and Radix Astragali preparata via network pharmacology and PI3K/Akt signaling pathway - Gong, Pin; Wang, Danni; Cui, Dandan; Yang, Qian; Wang, Peipei; Yang, Wenjuan; Chen, Fuxin (Phytomedicine (Stuttgart), 2021)
Radix Astragali (RA) consists of the dried root of Astragalus membranaceus Bunge and is one of the most frequently used dietetic Chinese herbs to treat inflammation and neurodegenerative disease among other conditions. Radix Astragali preparata (RAP) is a medicinal form of RA. RA and RAP have been used as anti-aging agent, however, the mechanisms underlying their effects are still unclear. Considering the wide application of RA and RAP in clinical practice, it is necessary to identify the better product between the two and elucidate the molecular mechanism responsible for their anti-aging effects. In this study, network pharmacology integrated with molecular biology techniques were employed to explore the possible mechanism of RA and RAP against aging. Aging animal models were constructed by exposure to D-galactose (D-gal), and the anti-aging effect of RA and RAP were determined based on behavior tests and histomorphological observation. Network pharmacology was performed to construct the “compound-target-pathway” network. Gene and protein expression of possible targets were validated and analyzed using qRT-PCR and Western blotting. Treatment by RA and RAP could alleviate the symptoms of aging such as a decrease in body weight and organ indices, behavioral impairment, increased oxidative stress, weaken histopathological evaluation. The effect of RAP was more pronounced than that of RA in preventing aging process in a mouse model. The anti-aging effect of RA and RAP is associated with the balance of oxidative stress and activation of PI3K/Akt signaling pathway. Using an integrated strategy of network pharmacology and molecular biology we attempted to elucidate the mechanisms of action of RA and RAP. [Display omitted]